Pengaruh CR dan ROA Terhadap Kebijakan Dividen Perusahaan Idx80 Periode 2019–2024 - amalia sapitri; Ratna Juwita (MDP Student Conference, 2026)
This study aims to analyze the effect of Current Ratio (CR) and Return on Assets (ROA) on Dividend Policy in companies listed on IDX 80 during the period 2019-2024. The method used in this study is a quantitative approach with multiple linear regression analysis. The sample consists of 44 companies selected using purposive sampling techniques, with a total sample of 261 samples. The results of the study indicate that, partially, the Current Ratio (CR) variable has a negative and significant effect on dividend policy, and Return on Assets (ROA) has a positive and significant effect on dividend policy. Simultaneously, the Current Ratio (CR) and Return on Assets (ROA) variables have a significant effect on dividend policy.